2011
DOI: 10.1095/biolreprod.110.088989
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Mouse Sperm Motility Patterns Using an Automated Multiclass Support Vector Machines Model1

Abstract: Vigorous sperm motility, including the transition from progressive to hyperactivated motility that occurs in the female reproductive tract, is required for normal fertilization in mammals. We developed an automated, quantitative method that objectively classifies five distinct motility patterns of mouse sperm using Support Vector Machines (SVM), a common method in supervised machine learning. This multiclass SVM model is based on more than 2000 sperm tracks that were captured by computer-assisted sperm analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 43 publications
10
154
1
Order By: Relevance
“…Vigorous sperm motility is absolutely necessary for normal fertilization in mammals. 36 We measured the sperm motility in AMH-atg5 ¡/¡ and Atg5 Flox/Flox mice by computer-assisted semen analysis and found that the sperm motility of AMHatg5 ¡/¡ mice (15.00 § 1.83%) was severely decreased compared to that of Atg5 Flox/Flox mice (88.00 § 1.83%) (Fig. 2G) (Fig.…”
Section: The Disruption Of Autophagy In Sertoli Cells Perturbed the Smentioning
confidence: 94%
“…Vigorous sperm motility is absolutely necessary for normal fertilization in mammals. 36 We measured the sperm motility in AMH-atg5 ¡/¡ and Atg5 Flox/Flox mice by computer-assisted semen analysis and found that the sperm motility of AMHatg5 ¡/¡ mice (15.00 § 1.83%) was severely decreased compared to that of Atg5 Flox/Flox mice (88.00 § 1.83%) (Fig. 2G) (Fig.…”
Section: The Disruption Of Autophagy In Sertoli Cells Perturbed the Smentioning
confidence: 94%
“…Motility parameters were analyzed in capacitated sperm from the different transgenic models using Hamilton-Thorne CASA system (Beverly, MA, USA) and CASAnova software as described (Goodson et al, 2011). Spontaneous and A23187 (10 µM)-induced acrosome reaction was measured as described (Wertheimer et al, 2008) in sperm from WT, Pyk2 −/− and Fer DR/DR mice.…”
Section: Motility and Acrosome Reaction Assaysmentioning
confidence: 99%
“…Sperm motility was then measured using the CEROS sperm analysis system (software version 12.3; Hamilton Thorne Biosciences, Beverly, MA). The analysis setting described previously (Goodson et al, 2011) was used. Sperm motility was also analyzed with an Olympus BX-53 microscope equipped with a highspeed camera (HAS-L1, Ditect, Tokyo, Japan).…”
Section: Sperm Motility Analysismentioning
confidence: 99%